The Costs and Benefits of Various Wage Bargaining Structures : An Empirical Exploration - Thomas, Alun (IMF Working Papers; Working Paper, 2002)
The literature on the relationship between the unemployment rate and wage bargaining fails to separate the offsetting effects of a reduction in competition associated with centralized bargaining and the increased awareness of unemployment externalities. This paper uses OECD data to distinguish these effects. While wages have become more sensitive to changes in the unemployment rate in countries that have switched to centralized wage-bargaining arrangements, the industry wage is not particularly sensitive to internal factors (relative price and productivity shifts) in economies with centralized/industry-level bargaining arrangements. The latter effect dominates in terms of persistently high unemployment and weaker growth.